(untitled) (INTERNATIONAL SEMINAR, 2025)
Rocket fins serve to stabilize a rocket during flight but are prone to flutter, necessitating an aeroelastic analysis to determine their susceptibility. This study presents the effect of bracket models’ inclusion in a computational aeroelastic analysis on a supersonic fin, and the effect on thermal loading of a supersonic fin resulting from a reduction of fin thickness from 25 mm to 12 mm. Using finite element models and the P–K method, flutter onsets were identified at Mach 11.0 for the bracket-free fin and Mach 10.6 for the fin with brackets, both values substantially exceeding the required design criterion of Mach 3.99. These results show that the inclusion of bracket models has only a marginal effect on aeroelastic behavior, while the thinner fin maintains structural stability. Thermal analyses further revealed that the 12-mm fin experiences lower surface temperatures than the 25-mm fin, possibly due to its smaller leading edge’s inclination angle. Future investigations should expand on structural loading scenarios to ensure comprehensive design validation.